Synthesis, Spectral and Thermal Studies of Some Dioxouranium(VI) Coordination Compounds of 4[N-(4-Hydroxy-3-Methoxybenzalidene) Amino] Antipyrine Semicarbazone and 4[N-(3,4,5-Trimethoxybenzalidene) Amino] Antipyrine Semicarbazone† - Singh, Lakshman; Singh, U.P.; Chkraborti, Indranil (Asian Journal of Chemistry, 2010)
In view of high coordination compounds formed by actinide metal ions, the present work describes the 8, 9 and 10-coordinated compounds of dioxouranium(IV) with 4[N-(4-hydroxy-3-methoxybenzalidene) amino] antipyrine sernicarbazone (HMBAAPS] and 4[N-(3,4,5-trimethoxybenzalidene) amino] antipyrine semicarbazone (TMBAAPS) with the general composition UO2X2·2L (X = Br-, I-, NCS- or CIO4-) and UO2X2·L (X = NO3-) or CH3COO- and L = HMBAAPS or TMBAAPS). All these complexes were characterized through elemental, spectral and thermal . studies.